Upaya Meningkatkan Hasil Belajar Matematika dengan Pendekatan TARL Bermedia Flashcard di Kelas 1 SD Muhammadiyah Birrul Walidain - Novia, Lisa Fidia; Purbasari, Imaniar; Noorwahyuni, Lisa (Indo-MathEdu Intellectuals Journal, 2025)
The low mathematics learning outcomes of grade I students in the measurement material show the need for a learning approach that is more in accordance with the stage of student development. The purpose of this research is to improve the learning outcomes of measurement materials through the application of the Teaching at the Right Level (TaRL) approach assisted by flash card media. The method of this research is Class Action Research (PTK) which is carried out in two cycles. Each cycle consists of planning, implementation, observation, and reflection. The subject of the study was the 1st grade students of SD Muhammadiyah Birrul Walidain with a total of 28 students. The instruments used include observation sheets, documentation and learning outcome tests. The results showed an increase in student learning completeness from 68% in the pre-cycle to 78% in the first cycle, and increased again to 92% in the second cycle. This improvement shows that the TaRL approach assisted by flash card media is effective in improving student learning outcomes in measurement materials. The conclusion of this study is that the application of the TaRL approach with flash card media can improve the mathematics learning outcomes of grade I students.